Analisis Beban Kerja dan Kebutuhan Karyawan (Direktorat Operasional Kantor Pusat) PT Perkebunan Nusantara VIII - Lestari, Puji; Trisyulianti, Erlin (IPB University, 2018)
The crisis of high labor cost leads companies to evaluate the number of employees in the head office. This study aims to determine the workload and needs of employees in the Directorate of Operations PT Perkebunan Nusantara VIII Head Office. The method used in this research is the analysis of the workload with the calculation of Full Time Equivalent (FTE) and work sampling using purposive sampling techniques. The ideal number of employees at the Directorate of Operations is 40 employees consisting of 21 employees of the Plant Department and 19 employees of the Engineering and Processing Department. Based on teh observation, employee working time in Directorate of Operations shows that the average of employee working time is 87,8 4percent fairly productive because it meets the standard that is above 85 percent.